2016
DOI: 10.1111/1755-5922.12230
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2C9 gene polymorphism and warfarin maintenance dosage in pediatric patients: A systematic review and meta‐analysis

Abstract: We found that CYP2C9 gene polymorphism (referring to the presence of *1/*2, *1/*3, and variant genotypes in the population in addition to the wild type) was significantly associated with decreased warfarin maintenance dose requirements. Additionally, a specific indication for warfarin, the Fontan procedure, was associated with a lower daily warfarin dose. However, the results of our study require confirmation from more research with larger numbers of pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Given the heterogeneity and variable quality of the studies included in the meta‐analyses, their conclusions are no more revealing or helpful in clarifying the confusion and can broadly be summarised as follows: The effectiveness of genotype‐guided dosing was dependent on the dosing strategy in non‐genotyped cohort (ie whether genotype‐guided dosing was compared with fixed dose strategy or with clinical algorithm‐guided dosing). In terms of PTTR, the principal measure of effectiveness, genotype‐guided strategy was superior to fixed‐dose strategy but not always so when compared with clinical algorithms. There was general agreement that carriers of the common CYP2C9 alleles ( CYP2C9*2 and *3 ) and VKORC1 allele ( VKORC1 1639G → A) required lower doses of warfarin. Although the majority of meta‐analyses found that genotype‐guided dosing improves PTTR, there was no unanimity. Genotype‐guided dosing led to shorter times to therapeutic INR and stable maintenance dose of warfarin. The findings on time‐sensitivity (onset and duration) of the effectiveness of genotype‐guided dosing, especially PTTR and risk of over‐anticoagulation, were ambiguous and were also sensitive to the dosing strategy in the control group. There was no unanimity on whether genotype‐guided therapy reduced the risk of over‐anticoagulation (INR > 4) with a number of meta‐analyses finding no benefit in terms of this risk. Although the presence of CYP2C9*3 variant appeared to be associated with higher risk of major bleeds, there was no unanimity on whether genotype‐guided dosing reduced bleeding. A majority of the meta‐analyses reported no benefit following the genotype‐guided dosing strategy in terms of thromboembolic events. There was unanimous agreement that arising from inter‐ethnic differences in prevalence of common variants, as well as ethnicity‐specific variants of CYP2C9 and VKORC1 , there are significant inter‐ethnic differences in maintenance doses of warfarin. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the heterogeneity and variable quality of the studies included in the meta‐analyses, their conclusions are no more revealing or helpful in clarifying the confusion and can broadly be summarised as follows: The effectiveness of genotype‐guided dosing was dependent on the dosing strategy in non‐genotyped cohort (ie whether genotype‐guided dosing was compared with fixed dose strategy or with clinical algorithm‐guided dosing). In terms of PTTR, the principal measure of effectiveness, genotype‐guided strategy was superior to fixed‐dose strategy but not always so when compared with clinical algorithms. There was general agreement that carriers of the common CYP2C9 alleles ( CYP2C9*2 and *3 ) and VKORC1 allele ( VKORC1 1639G → A) required lower doses of warfarin. Although the majority of meta‐analyses found that genotype‐guided dosing improves PTTR, there was no unanimity. Genotype‐guided dosing led to shorter times to therapeutic INR and stable maintenance dose of warfarin. The findings on time‐sensitivity (onset and duration) of the effectiveness of genotype‐guided dosing, especially PTTR and risk of over‐anticoagulation, were ambiguous and were also sensitive to the dosing strategy in the control group. There was no unanimity on whether genotype‐guided therapy reduced the risk of over‐anticoagulation (INR > 4) with a number of meta‐analyses finding no benefit in terms of this risk. Although the presence of CYP2C9*3 variant appeared to be associated with higher risk of major bleeds, there was no unanimity on whether genotype‐guided dosing reduced bleeding. A majority of the meta‐analyses reported no benefit following the genotype‐guided dosing strategy in terms of thromboembolic events. There was unanimous agreement that arising from inter‐ethnic differences in prevalence of common variants, as well as ethnicity‐specific variants of CYP2C9 and VKORC1 , there are significant inter‐ethnic differences in maintenance doses of warfarin. …”
Section: Resultsmentioning
confidence: 99%
“…Two meta‐analyses referred to earlier comment on the potentially important role of the indication in genotype‐guided warfarin therapy; Fontan procedure (a surgical procedure for a special type of congenital cardiac disorder) was associated with lower dose in paediatric patients. This finding is interesting since a recent study has also reported that CYP2C9 and VKORC1 genotype‐guided dosing of warfarin may be beneficial in patients diagnosed with AF but not in patients with deep vein thrombosis or pulmonary embolism .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Warfarin maintenance doses in pediatric patients were in part dependent on the CYP2C9 genotype (*2 and *3 were 15% to 41% lower compared to the wild type), butand again reflection the specific issues in pediatric pharmacology-the Fontan procedure as a medical indication was also associated with a lower maintenance dose. 55 Intriguingly, CYP2C9 polymorphisms (rs2153628 and rs179985) were also associated with differences in the likelihood to response to indomethacin among preterm neonates with a patent ductus arteriosus, so that altered indomethacin metabolism may explain some of the variability in indomethacin disposition and response. 56 This puts the earlier mentioned paper of Lewis et al 32 on the relevance of prolonged urine collection to assess drug metabolism into additional perspective.…”
Section: Developmental Toxicity and Phase I Ontogenymentioning
confidence: 99%
“… investigated the possible impact of patient deconditioning and vitamin K intake or fasting upon the INR response to warfarin. Since 2010, 13 original studies and two meta‐analyses focused on warfarin pharmacogenomics have been published, and these were identified with this search strategy. Data synthesis of these studies confirms that the identified vitamin K epoxide reductase complex subunit 1 ( VKORC1 ) and cytochrome P450 2CP ( CYP2CP ) variants probably contribute to a reduction in warfarin dosing requirements as compared with wild‐type alleles; however, all studies were conducted in patients with warfarin steady states, and most studies had small cohorts with limited ethnic diversity.…”
Section: Anticoagulant Therapy: Which Agent Intensity and Duration?mentioning
confidence: 99%